2009
DOI: 10.1089/pho.2008.2394
|View full text |Cite
|
Sign up to set email alerts
|

Cavity Preparation and Influence of Restorative Materials on the Prevention of Secondary Caries

Abstract: There was less development of caries lesion around LA-prepared cavities than around the DB-prepared cavities; however, no synergistic cariostatic effect was observed between the Er:YAG laser and glass ionomer cement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
1
22
0
2
Order By: Relevance
“…The findings of this study confirmed the outcomes of Hossain et al 16 who found that the quantities of calcium (Ca weight %) and phosphorus (P weight %) of dentin were significantly greater in laser cavities compared to bur cavities. Perito et al 15 reported less development of secondary caries around the cavities prepared by Er:YAG laser than around bur-prepared cavities. In contrast, Celik et al 28 found that cavity preparation with bur or erbium family lasers did not significantly affect the composition and microhardness of dentin structure.…”
Section: Discussionmentioning
confidence: 98%
“…The findings of this study confirmed the outcomes of Hossain et al 16 who found that the quantities of calcium (Ca weight %) and phosphorus (P weight %) of dentin were significantly greater in laser cavities compared to bur cavities. Perito et al 15 reported less development of secondary caries around the cavities prepared by Er:YAG laser than around bur-prepared cavities. In contrast, Celik et al 28 found that cavity preparation with bur or erbium family lasers did not significantly affect the composition and microhardness of dentin structure.…”
Section: Discussionmentioning
confidence: 98%
“…Fluorides may also be released from restorative materials as a preventive method. [1][2][3][4][5] Among them, adhesives and composite resins (CR) seem to provide little or no cariostatic effect. 3 On the other hand, conventional glass ionomer cements (GI) have shown the highest cariostatic potential, and glass ionomer/resin composite hybrid materials (RM) have shown an intermediate effect on caries prevention.…”
Section: Introductionmentioning
confidence: 99%
“…3 On the other hand, conventional glass ionomer cements (GI) have shown the highest cariostatic potential, and glass ionomer/resin composite hybrid materials (RM) have shown an intermediate effect on caries prevention. [3][4][5] Several in vitro studies have suggested the use of highintensity lasers at low doses, such as erbium and CO 2 , as a tool in the prevention of dental caries. [5][6][7][8][9][10] Some in vitro and in situ studies were able to demonstrate the potential of erbium lasers to increase enamel acid resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, pH cycle experiments simulate oral cariogenic conditions and are conducted to provide information regarding enamel demineralization of restorative materials and adhesives used in cavity preparation techniques. 4,23 The objective of this study was to evaluate the inhibition of enamel demineralization around restorative materials after QTH, LED, or AL activation according to the Knoop microhardness (KHN) profile of the enamel and the indirect degree of conversion in the superficial and deep areas of restorative materials.…”
mentioning
confidence: 99%